The effects of L-carnitine supplementation in athletic performance - Oliveira, C.; Sousa, M. (Science & Sports, 2019)
Objectives: This review aims to analyze the available data, mainly the most recent, regarding L-carnitine supplementation and exercise performance, in order to understand if L-carnitine can still be considered an ergogenic supplement. Moreover, it also aims to briefly analyze other potential uses, more specifically the effects on weight loss, recovery after exercise and aging. News: A literature search, using the online scientific databases PubMed and Scopus, was conducted to identify studies related to L-carnitine supplementation and athletic performance. The discovery that skeletal muscle carnitine content can be increased through oral supplementation in humans represented a significant progress in this area. More recently, due to this discovery, new research has been done to investigate whether L-carnitine supplementation could have an impact on fuel metabolism. However, the inconsistency of results led to a change in the focus of research, shifting towards the investigation of the impact L-carnitine could have on the process of recovery after exercise and on aging. Prospects and projects: In future research, this new area needs to be more explored. Nevertheless, the study of the L-carnitine supplementation impact on fuel selection during exercise should continue and it is crucial to use athletes. Conclusion: Despite some performance benefits have been demonstrated, more research needs to be done. Presently, the available data is still not enough to widely recommend the use of L-carnitine supplements with the aim of improving exercise performance.